In Vitro Activities of Telithromycin (HMR 3647) against Rickettsia rickettsii, Rickettsia conorii, Rickettsia africae, Rickettsia typhi, Rickettsia prowazekii, Coxiella burnetii, Bartonella henselae, Bartonella quintana, Bartonella bacilliformis, and Ehrlichia chaffeensis - Rolain, Jean-Marc (American Society for Microbiology, 2000)
In vitro activities of telithromycin compared to those of erythromycin against Rickettsia spp., Bartonella spp., Coxiella burnetii, and Ehrlichia chaffeensis were determined. Telithromycin was more active than erythromycin against Rickettsia, Bartonella, and Coxiella burnetii, with MICs of 0.5 μg/ml, 0.003 to 0.015 μg/ml, and 1 μg/ml, respectively, but was inactive against Ehrlichia chaffeensis.